Congenital Erythropoietic Porphyria With Calcific Constrictive Pericarditis: A Case Report and Brief Review of Literature. (October 2015) - Chowdhury, Ujjwal K.; Patel, Kartik; Seth, Sandeep; Ray, Ruma; Jagia, Priya; Sahu, Manoj
An 18-year-old boy with congenital erythropoietic porphyria and calcific constrictive pericarditis underwent total pericardiectomy. The cause of pericardial calcification could be deposition of porphyrins in the pericardium. Surgical importance of this rare condition is highlighted.